Hazard Identification, Risk Assessment, and Determining Control (HIRADC) for Workplace Safety in Manufacturing Industry: A Risk-Control Framework Complete with Bibliometric Literature Review Analysis to Support Sustainable Development Goals (SDGs) - H. Henny; Agus Heri Setya Budi; Muhammad Andriyansyah; Muhammad Rizzki Ar Rozzak; Maretno Marcelina Baru; Alias Masek (Bumi Publikasi Nusantara, 2025)
This study implements the Hazard Identification, Risk Assessment, and Determining Control (HIRADC) method to evaluate and mitigate occupational risks in the manufacturing construction sector. A bibliometric analysis reveals a growing yet insufficient number of studies applying structured risk control frameworks like HIRADC in industrial settings, particularly in developing countries. Using a descriptive approach, data were collected through field observations, interviews, and document analysis. Seven hazards were identified, resulting in five low-risk and two moderate-risk classifications using a probability–severity matrix. Control measures were implemented following ISO 45001:2018 standards, including engineering controls, administrative actions, and personal protective equipment (PPE). The results demonstrate that HIRADC enhances workplace safety awareness and reduces risk levels. This study contributes a practical safety framework for manufacturing environments while reinforcing the relevance of SDG-aligned and bibliometrically justified research in occupational health.